A Collaborative Design and Modularized Assembly for Prefabricated Cabin Type Energy Storage System With Effective Safety Management - Chen, Chen; Lai, Jun; Guan, Minyuan (Frontiers in Energy Research, 2022)
With the deepening of the electricity marketization mechanism, the demand for large-capacity electrochemical energy storage technology represented by prefabricated cabin energy storage systems by power grid companies has further expanded. However, prefabricated cabins are significantly different from grid energy storage requirements in terms of process, technology, and quality, resulting in difficulty in quality control, heavy workload in later operation, and high safety risks. There is an urgent need to develop modular and universal energy storage device integration technology. With the core objective of improving the intrinsic safety of energy storage devices, this paper investigates the intrinsic safety technology of energy storage devices based on key material modification, the intelligent autonomy technology of energy storage devices with panoramic monitoring, and the design and testing technology of modular universal energy storage prefabricated cabins based on safety orientation. An accurate failure model for lithium-ion and lead-carbon batteries is proposed, online monitoring of the battery failure process, online monitoring of the panoramic view of the energy storage device, and a safety-oriented design of a modular universal energy storage prefabricated cabin. The research results of this paper could help to improve the maturity and industrialization level of energy storage devices, maximize the safety and reliability of energy storage devices, and lay the foundation for the deepening application and promotion of energy storage technology.